2011
DOI: 10.1080/09654313.2011.548369
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimum Environmental Conservation: Using Multi-Criteria Decision-Making Techniques

Abstract: The type and degree of conservation areas in Turkey legally dictate the kind of land uses that can and cannot take place in a conservation area. Thus, the conservation scheme is one of the most important criteria in designing an urban land-use plan. The aim of this study is to analyse the effects of various conservation decisions on land-use allocation holding everything else constant. This study uses a land-allocation mathematical programme formulated by Hanink and Cromley [(1998) Land-use allocation in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Pixels that contain a value above a suitability threshold represent optimal locations. GIS-based MCA has been applied to a number of land use suitability mapping applications, for example in land allocation for planning (Hanink and Cromley, 1998), natural wastewater treatment (Anagnostopoulos et al, 2009), bicycle facility planning (Rybarczyk and Wu, 2010) and conservation effects on urban landuse planning (Çelik and Türk, 2011). Other biological examples include evaluation of land suitability for giant prawn farming (Macrobrachium rosenbergii -Hossain and Das, 2010), planning for biodiversity assets (Geneletti, 2008) the identification of suitable habitat for the old-forest polypore (Skeletocutis odora - Store and Kangas, 2001), or for black bear (Ursus americanus) habitat (Clevenger et al, 2002).…”
Section: Multi-criteria Analysis (Mca)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pixels that contain a value above a suitability threshold represent optimal locations. GIS-based MCA has been applied to a number of land use suitability mapping applications, for example in land allocation for planning (Hanink and Cromley, 1998), natural wastewater treatment (Anagnostopoulos et al, 2009), bicycle facility planning (Rybarczyk and Wu, 2010) and conservation effects on urban landuse planning (Çelik and Türk, 2011). Other biological examples include evaluation of land suitability for giant prawn farming (Macrobrachium rosenbergii -Hossain and Das, 2010), planning for biodiversity assets (Geneletti, 2008) the identification of suitable habitat for the old-forest polypore (Skeletocutis odora - Store and Kangas, 2001), or for black bear (Ursus americanus) habitat (Clevenger et al, 2002).…”
Section: Multi-criteria Analysis (Mca)mentioning
confidence: 99%
“…The knowledge elicitation procedure through pairwise comparison is followed in Hanink andCromley (1998), Clevenger et al (2002), Hossain and Das (2010) and Çelik and Türk (2011) and subsequent suitability mapping is a stage shared by all of the stated examples. Clevenger et al (2002) developed an expert-based model (using 2 experts) and a literature-based model, with the latter found to be the closest estimate to an empirical model that the authors had developed.…”
Section: Spatial Analysismentioning
confidence: 99%
“…Cromley and Hanink (1999) argue that the use of heuristics, such as MOLA, for tackling spatial problems is only justified if they result in near optimal solutions and if an efficient exact method cannot be developed. Consequently, they demonstrated that suitability based land use allocation analysis can be operationalized in terms of a generalized assignment problem (see also Çelik and Türk 2011;Türk and Çelik 2013) and solved using exact methods (see Chap. 5).…”
Section: Site Suitability Heuristicsmentioning
confidence: 99%